The impact of heavy metals Pb and Hg on protein metabolism of species of the genus Acer L. in the conditions of planned factorial experiment - Поворотня, М. М. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology»)
The effect of heavy metals (mercury and lead) on protein metabolism in leaves of species of the genus Acer was investigated in the conditions of planned factorial experiment. The inhibitory effect of heavy metals on protein content was revealed in leaves. Тhe mathematical model building using regression equations allows to determine the intensity of the impact of heavy metals on protein content in leaves and nature of this effect: inhibiting or stimulating. The coefficients of the regression equations quantitatively demonstrate the negative effect of mercury and lead separately and together, that qualitatively distinguishes this method from conventional methods of empirical data without quantitative assessment of impacts. Protein synthesis system was more sensitive to the mercury salts in solution than to the lead salts. The prospects of planned factorial experiment in the study of the influence of heavy metals on physiological and biochemical indexes of plants was justified. The most resistant species of maple were defined for using in gardening areas in conditions of anthropological and technological pressure with a high content of heavy metals.